Tinjauan Yuridis Pembatalan Wakaf Oleh Nadzir(Studi Kasus di Pengadilan Agama Surakarta) - Widiyanto, Eko Mei; , Mutimatun Ni'ami, S.H., M.Hum; , Darsono, S.H., M.H (2016)
This study aims to determine the legal considerations by the judge in case of cancellation of endowments performed by nadzir and to know the status of the object after canceled by nadzir endowments. This research method through empirical juridical approach to data sources in the form of secondary data that is the source of primary law, secondary and tertiary and primary data in the form of interviews. Data were collected by literature study and interviews. Data analysis techniques with qualitative analysis. The results showed that the legal considerations by the judge in case of cancellation of endowments performed by nadzir that is based on facts that have been discovered in the trial, linked with written proof or evidence of witnesses who support each other, which is based on the provisions of Article 3 of Law No. 41 of 2004 on endowments, which He swore that the endowment can not be canceled and the decision is in conformity with the provisions of existing law and does not conflict with Personality '. While the status object was canceled by nadzir endowment after the waqf land remains the property Assegaf Surakarta Masjid in accordance with Article 3 of Law No. 41 of 2004.